Informational and entropic analysis of the spatial distribution of galaxies - Nayrzbayeva, A.Z.; Kassymkhanova, G.S.; Konysbayev, T.K. (Recent Contributions to Physics, 2016)
Despite the great progress made recently in describing the properties of structure in the Universe, and the question of its formation, there are still many unsolved issues in this area, among which in particular the question of the lower border of the scale on which the universe becomes uniform. In this work, based on the data of the equatorial coordinates and the redshifts of galaxies, resulting from the implementation of projects Sloan Digital Sky Survey and 2dF Galaxy Redshift Survey, was carried out of informational and entropic analysis of the structure of the universe at different scales. It was found that the normalized entropy of the spatial distribution of galaxies increases in the values ​​of 0.65 on the scale of 15-20 Mpc to 0.9 on the scale of 110 Mpc, approaching, but not reaching, the entropy values ​​of a uniform distribution even at 150 Mpc. Thus, our researches suggests that some structural in the universe should be observed for at least up to the scale of 150 Mpc.